Application of Microcontroller-Based Temperature and Humidity Control Technology with Internet of Things (IoT) System in Betuah Mushroom MSMEs: Penerapan Teknologi Pengatur Suhu Dan Kelembapan Berbasis Mikrokontroller DenganSistem Internet Of Things(Iot)Pada UMKM Jamur Betuah - Padil, Padil; Febrizal, Febrizal; Eteruddin, Hamzah; Dini, Isna Rahma; Huda, Feblil (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Temperature and humidity in the barn greatly affect the growth of oyster mushrooms. Therefore, it is necessary to keep air circulation inside the barn optimised. Betuah mushroom SMEs faces the difficulties in controlling both optimum temperature and humidity for oyster mushroom growth. Therefore, this serviceaims to utilise Internet of Thing (IoT) technology to regulate temperature and humidity for oyster mushroom cultivation using DHT22 sensors in Betuah mushroom MSMEs located in Tuah Madani District, Pekanbaru City. The stages of the method used include socialisation, training, technology application, mentoring and evaluation and program sustainability. From the service carried out, microcontroller-based automatic temperature and humidity control technology with an IoT system was successfully applied. The resulting tool can control the temperature and humidity in the barn according to the set limits. The produced products improved in terms of quality, which the oyster mushroom's both flesh and color is respectively not hard nor yellow. The quantity of fresh mushrooms produced is stable and increasing per day, ranging from 15-20 kg/day to 20-30 kg/day production